TECHNOLOGY CAN HELP: CHILDREN COMMENT ON COMPUTERS - McLean, Margaret (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1988)
Although there are several studies which have documented how computers are used in schools, there has been relatively little research which has considered children’s perceptions of computers. This paper presents results from interviews with elementary grade students to find out what they thought about computers and learning, what uses they saw for them inside and outside school, and what difficulties they had with them. Their comments are grouped into three areas: computer as tool, collaborative learning, and dealing with difficulties. Implications of their perceptions in these areas are discussed. RÉSUMÉ Bien qu’il y ait plusieurs études consacrées à l’utilisation des ordinateurs à l’école, les recherches portant sur la perception des ordinateurs par les enfants sont relativement rares. Dans cet article, l’auteur présente les résultats d’entrevues qu’il a eues avec des élèves du primaire pour savoir ce qu’ils pensaient des ordinateurs et de l’apprentissage, quels usages ils prévoyaient en faire à l’intérieur comme à l’extérieur de l’école et les problèmes que cela leur posait. Leurs observations sont regroupées en trois sections: l’ordinateur comme instrument, l’apprentissage en collaboration et la résolution des difficultés. L’auteur analyse alors les conséquences de leur perception dans ces secteurs.